Can the traditional use of native plant species in rural communities in the Brazilian semi-arid region be affected by global warming? - Farias Lima, José Ribamar; Nunes Carvalho, Thamires Kelly; Santos Souza, Ramon; Hart, Robbie; W. Bussmann, Rainer; Fernandes Magalhães, Henrique; da Silva Oliveira, Regina Célia; Farias Paiva de Lucena, Reinaldo (Ethnobiology and Conservation, 2023)
Extreme climate change events are capable of modifying the physiognomy of landscapes, impacting millions of people around the world. Consequently, the traditional knowledge of people residing in these regions about local natural resources may also be affected. To identify how the traditional use of native plant species can be influenced by a change in the availability of these species in a rural community in a semi-arid region, in a scenario of climatic extremes, we developed a Pressure Indicator for Use Preference (PIUP), seeking to identify the species under the greatest pressure of use. The study was carried out in the São Francisco Rural Community, in the Cabaceiras Municipality, in the semi-arid region of the Paraíba State, with 42 local informants. The species with the highest PIUP had their potential distribution for the year 2050 modeled using the HadGEM2-ES climate model under the RCP4.5 scenario, as an optimistic forecast, and the RCP8.5 scenario, as a pessimistic forecast. The construction of the models identified a potential increase in the coverage area of ​​all analyzed species, with a greater territorial extension for the RCP8.5 scenario. Myracrodoun urundeuva, Mimosa tenuiflora and Croton blanchetianus were the species with the lowest potential area growth for the year 2050. The high use of species, especially M. urundeuva, associated with reduced growth in a more arid environment is a worrying factor for the population structure of the species, as well as for rural communities that make representative use of the species.